The Effects of Digital Learning on International Schools’ Curriculum in Kenya (African Multidisciplinary Journal of Research, 2025)
This desktop review reconceptualizes Sustainable Development Goal 4 (quality education) by examining digital learning’s impact on Kenyan international schools’ curricula. Analysing 15 Kenyan peer-reviewed studies (2019–2024) and OECD reports, we identify cognitive-pedagogical trade-offs: digital tools boost STEM engagement and collaboration (e.g., 25% KCSE gains via hybrid models) but risk fragmenting literacy and critical thinking in humanities due to screen-based distractions. Sweden’s evidence-led recalibration—prioritizing print for core literacy/math and digital tools for specialized tasks—reversed comprehension declines by 12%, offering Kenya a model for balancing innovation with foundational skills. Systemic gaps persist in Kenya, including urban-rural access divides, under-resourced teacher training, and low parental digital literacy, which exacerbate inequalities and threaten holistic development. To advance SDG 4 amid today’s technological challenges, we propose a participatory hybrid framework: (1) strategic screen-time governance (capping digital exposure at 30% for early literacy), (2) AI-augmented adaptive learning with ethical safeguards, and (3) community co-designed partnerships to align emerging technologies with localized needs. Case studies (e.g., Braeburn School’s print-digital scheduling; Trans Nzoia’s solar-powered tablets + story circles) demonstrate 15–25% academic gains and 90% student satisfaction when blending low- and high-tech methods. We urge policymakers to leverage strategic communication for stakeholder buy-in, emerging media technologies for equitable resource distribution, and AI governance to ensure tools serve pedagogical—not just technological—ends. Findings advocate for phased hybrid rollouts, teacher capacity building in blended facilitation, and parent-involved digital literacy initiatives to foster inclusive, future-ready education systems that reconcile SDG targets with tomorrow’s possibilities.